2016
DOI: 10.1161/hypertensionaha.116.08227
|View full text |Cite
|
Sign up to set email alerts
|

High-Normal Estimated Glomerular Filtration Rate in Early-Onset Preeclamptic Women 10 Years Postpartum

Abstract: Abstract-Women with a history of preeclampsia have a 5-to 12-fold increased risk to develop end-stage kidney disease.Previous observations in small cohorts suggest that former preeclamptic (fPE) women have subtle abnormalities in renal hemodynamics and renal function, which might predispose them to renal failure in later life. In this study, we analyzed renal function in a cross-sectional cohort consisting of former early-onset preeclamptic (fPE, n=339) and former healthy pregnant women (fHP, n=332), overall w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…Specifically, while copeptin was not associated with SBP in patients with prior PE, we observed a positive association in healthy controls, in line with prior evidence aside from pregnancy ( 28 ). A similar modulating effect of PE was observed regarding the relationship between copeptin and eGFR, although clinical interpretation is rendered tedious by the glomerular hyperfiltration described in the post-partum period whether after PE or a healthy pregnancy ( 37 , 38 ).…”
Section: Discussionsupporting
confidence: 55%
“…Specifically, while copeptin was not associated with SBP in patients with prior PE, we observed a positive association in healthy controls, in line with prior evidence aside from pregnancy ( 28 ). A similar modulating effect of PE was observed regarding the relationship between copeptin and eGFR, although clinical interpretation is rendered tedious by the glomerular hyperfiltration described in the post-partum period whether after PE or a healthy pregnancy ( 37 , 38 ).…”
Section: Discussionsupporting
confidence: 55%
“…Previous studies report on kidney function in women with a history of HDP at different set time points postpartum, mostly shortly after preeclampsia, and show either subtle alterations or no differences in kidney function and kidney hemodynamics. [7][8][9][10][11] At 10 years postpartum, a high-normal eGFR is reported in women with a history of preterm preeclampsia, 9,21 which is speculated to represent a state of hyperfiltration as compensation for loss in kidney function leading to kidney function loss in the long term. In the present study, we observed a slightly lower eGFR instead of a high-normal eGFR, which might be explained by the approximately 10-year older age at the start of follow-up, during which hyperfiltration is not compensating for loss in kidney function anymore.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of the long-term effect of p-AKI on the future development of CKD is limited. However, there is a growing number of studies addressed to describing the relationship between PE and the hypertensive disorders of pregnancy and the development of cardiovascular diseases and CKD [ 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 ]. The data from the literature are somewhat conflicting, as a result of the heterogeneity of the studies and the differences in the definitions they adopt.…”
Section: The Effect Of Aki and The Hypertensive Disorders Of Pregnmentioning
confidence: 99%